Complex method of surface hardening of steel P6M5 by nitro-titanizing and nitro-chromizing discrete laser treatment - Хижняк, В.Г.; Кіндрачук, М.В.; Загребельний, В.В. (Problems of Tribology, 2016)
It is considered the structure, phase and chemical composition, microhardness and microfragility of surface areas of steel P6M5 after chemical - thermal treatment: nitriding with further titanizing and chromizing. It is shown the dependence of physical and mechanical properties of complex coatings and discrete laser treatment on wear-resistance. Results analysis shows that nitro-chromized coating on laser treated steel used as coating substrate is characterized by highest wear-resistance under sliding friction conditions.